The Patient Health Questionnaire-9 vs. the Hamilton Rating Scale for Depression in Assessing Major Depressive Disorder - Ma, Simeng; Yang, Jun; Yang, Bingxiang; Kang, Lijun; Wang, Peilin; Zhang, Nan; Wang, Wei; Zong, Xiaofen; Wang, Ying; Bai, Hanping; Guo, Qingshan; Yao, Lihua; et al. (Frontiers in Psychiatry, 2021)
Background: The Hamilton Rating Scale for Depression (HAMD-17) has been used for several decades to assess the severity of depression. Multiple studies have documented defects in this scale and deemed it unsuitable for clinical evaluation. The HAMD-6, which is the abbreviated version of HAMD-17, has been shown to be effective in assessing the core symptoms of depression with greater sensitivity than HAMD-17. And the Patient Health Questionnaire-9 (PHQ-9) is suggested as an effective alternative to the HAMD-17 because of its simplicity and ease-of-use. Methods: Research was completed involving 1,741 participants having major depressive disorder. Cronbach's alpha, intraclass correlation coefficient (ICC) and weighted Kappa analysis was used to determine the reliability of the scales. Pearson correlation analysis and factor analysis were used to analyze validity. Item response theory (IRT) was used to analyze psychological characteristics of items in both the HAMD-17 and PHQ-9. Results: Reliability analysis showed that the Cronbach's alpha of the HAMD-17, HAMD-6 and PHQ-9 were 0.829, 0.764, and 0.893 respectively, and the ICC of the three scales ranged from 0.606 to 0.744. The Kappa score of the consistency of depression severity assessment was 0.248. Validity analysis showed that the PHQ-9 was a single factor structure, and the total score of the scale was strongly correlated with the HAMD-17 (r = 0.724, P < 0.001). The IRT analysis showed that the discrimination parameters of the PHQ-9 were higher than that of the HAMD-17 in all dimensions. The HAMD-6 had the lowest measurement accuracy in distinguishing the severity of depression, while the PHQ-9 had the highest measurement accuracy. Conclusion: Results showed that the PHQ-9 was satisfactory in terms of reliability, validity and distinguishing the severity of depression. It is a simple, rapid, effective and reliable tool which can be used as an alternative to the HAMD-17 to assess the severity of depression.